Parapneumonic pleural effusion: reality and strategies in an Amazon university hospital - ARÊAS,CLAUDIA GISELLE SANTOS (2016)
ABSTRACT Objective: to define the profile and analyze the postoperative evolution of children with parapneumonic pleural effusion (PPE), and to evaluate strategies used in the presence of diagnostic and therapeutic limitations, emphasizing the open thoracic drainage (OTD) . Methods: we conducted a cross-sectional, prospective, analytical study in which we followed children admitted in an Amazon university hospital with surgically addressed PPE, from October 2010 to October 2011. Results: we studied 46 patients, most children under three years of age (74%), with no gender predominance. A significant portion of the sample (28%) had inappropriate body mass index. We found short stature in five patients (11%), which tended, in general, to a worst postoperative outcome when compared with children of normal height (p=0.039). The average duration of symptoms till admission was 16.9 days. Empyema was a common diagnosis in the first surgery (47.8%), and its bearers had longer duration of chest tube drainage (p=0.015). Most children (80.4%) were operated only once. The mean length of hospital stay was 25.9 days. Thoracic drainage (water-sealed) was the most common procedure (85%), with conversion to OTD in 24% of the sample, thoracotomy being rare (4%). There were no deaths. Conclusion: the studied individuals often had advanced disease and nutritional disorders, affecting outcome. OTD remains a valid option for specific situations, and further studies are needed for confirmation.